Carbon Quantum Dots Modified Polyurethane Nanocomposite as Effective Photocatalytic and Antibacterial Agents - Kováčová, Mária; Marković, Zoran M; Humpolíček, Petr; Mičušík, Matej; Švajdlenková, Helena; Kleinová, Angela; Danko, Martin; Kubát, Pavel; Vajďák, Jan; Capáková, Zdenka; Lehocký, Marián; Münster, Lukaš; et al. (ACS biomaterials science & engineering, 2018)
Development of new types of antibacterial coatings or nanocomposites is of great importance due to widespread multidrug-resistant infections including bacterial infections. Herein, we investigated biocompatibility as well as structural, photocatalytic, and antibacterial properties of photoactive hydrophobic carbon quantum dots/polyurethane nanocomposite. The swell-encapsulation-shrink method was applied for production of these nanocomposites. Hydrophobic carbon quantum dots/polyurethane nanocomposites were found to be highly effective generator of singlet oxygen upon irradiation by low-power blue light. Analysis of conducted antibacterial tests on Staphyloccocus aureus and Escherichia coli showed 5-log bactericidal effect of these nanocomposites within 60 min of irradiation. Very powerful degradation of dye (rose bengal) was observed within 180 min of blue light irradiation of the nanocomposites. Biocompatibility studies revealed that nanocomposites were not cytotoxic against mouse embryonic fibroblast cell line, whereas they showed moderate cytotoxicity toward adenocarcinomic human epithelial cell line. Minor hemolytic effect of these nanocomposites toward red blood cells was revealed.
Keywords: photocatalytic activity; visible light sterilization; reactive oxygen species production; hydrophobic carbon quantum dots; antibacterial activity; polyurethane